Holiness as friendship with Christ: Teresa of Avila - Tara K. Soughers (HTS Teologiese Studies/Theological Studies, 2016)
Teresa of Avila, writing in the 16th century when ideas of holiness often excluded women and lay people, developed a radically inclusive understanding of holiness as friendship with Christ. Her idea also allowed for degrees of holiness, from those who completed only the necessary church requirements of confession and absolution all the way up to those who had a friendship that was modelled upon the relationship in the Song of Songs. It was a definition of holiness applicable to men and women, clergy, members of religious orders, and lay people. In addition, her understanding of holiness did not distinguish the holiness of ordinary lay people from that of the great saints of previous generations, for friendship with Christ was open to all.